1993
DOI: 10.1159/000263746
|View full text |Cite
|
Sign up to set email alerts
|

In utero Treatment of Toxoplasmic Fetopathy with the Combination Pyrimethamine-Sulfadiazine

Abstract: The mothers of 52 fetuses with toxoplasma fetopathy diagnosed in utero were treated with a combination pyrimethamine-sulfa drug and spiramycine. Their infants were compared to a group of 51 infants whose mothers had received spiramycine alone. Postnatal treatment was identical in both groups. Parasitological investigation of the placenta was positive in 42 and 76.6%; the newborns had a specific IgM of 17.4 and 69% in groups 1 and 2, respectively. These differences were significant. The mean specific IgG titer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
4

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 6 publications
5
39
0
4
Order By: Relevance
“…In a study of 542 pregnancies in which spiramycin was given to women who seroconverted during pregnancy (388 women given treatment and 154 without treatment) the percentage of children without prenatal infection increased from 39 to 77%, and the percentage of children with severe congenital disease or intrauterine death decreased from 11 to 3% [214]. If transmission to the foetus can be documented in utero (by polymerase chain reaction (PCR) or other techniques [33]) the administration of pyrimethamine and sulfadiazine to the mother can treat the infection in utero and further decrease the severity of symptoms in infected children [216,217].…”
Section: Congenital Toxoplasmosismentioning
confidence: 99%
See 2 more Smart Citations
“…In a study of 542 pregnancies in which spiramycin was given to women who seroconverted during pregnancy (388 women given treatment and 154 without treatment) the percentage of children without prenatal infection increased from 39 to 77%, and the percentage of children with severe congenital disease or intrauterine death decreased from 11 to 3% [214]. If transmission to the foetus can be documented in utero (by polymerase chain reaction (PCR) or other techniques [33]) the administration of pyrimethamine and sulfadiazine to the mother can treat the infection in utero and further decrease the severity of symptoms in infected children [216,217].…”
Section: Congenital Toxoplasmosismentioning
confidence: 99%
“…Women who seroconvert during pregnancy should be treated with spiramycin, and if transmission to the foetus is documented, they should be treated with pyrimethamine and sulfadiazine. Once born, all children of mothers who seroconverted during pregnancy should be evaluated for congenital toxoplasmosis and treated if infection is still evident [214,[217][218][219][223][224][225][226][227][228][229][230][231]]. …”
Section: Congenital Toxoplasmosismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on the effectiveness of pyrimethamine and sulfadiazine for the treatment of congenital T. gondii infections in humans, however, have been scarce. Those studies that have been reported in the literature are from France (10,11,20). Those studies described the effectiveness of treatment with pyrimethamine and sulfadiazine after fetal infection had been proven.…”
mentioning
confidence: 99%
“…The combination of pyrimethamine and sulphadiazine is highly active against T. gondii and is the most widely used treatment for prenatal infection (Hohlfeld et al 1989, Couvreur et al 1993, Villena et al 1998. Moreover, this combination is assumed to have a higher potential than spiramycine in reducing the risk of clinical manifestations in infected children (Foulon et al 1999, SYROCOT Study Group 2007).…”
Section: What Are the Current Practices?mentioning
confidence: 99%